The role of non-hematopoietic stromal cells in the persistence of inflammation - Barone, Francesca; Nayar, Saba; Buckley, Chris (Frontiers in Immunology, 2013)
Inflammation results from the complex interaction between hematopoietic and stromal cells and growing evidence supports a key role for the stroma in driving the switch from acute resolving to persistence in chronic inflammatory diseases. Stromal cells have also been shown to play a critical role in cancer biology, being involved in cancer growth, dissemination, and inhibition of the autologous immune response, ultimately favoring persistence and metastatic spread. Similarly, blood and lymphatic endothelial cells contribute to tissue homeostasis during physiological inflammation but also lead to discorded leukocyte and tumor cell accumulation in pathological inflammation and cancer. This review aims to summarize the role that pathogenic stroma plays in the pathogenesis of diseases such as cancer and chronic inflammation.